A perturbation approach for the dynamic analysis of one stage gear system with uncertain nnparameters. (October 2015) - Guerine, A.; El Hami, A.; Walha, L.; Fakhfakh, T.; Haddar, M.
Abstract: This paper addresses the dynamic response of a one stage gear system with uncertain parameters. The conventional methods dealing with stochastic systems are based on series expansion of stochastic quantities with respect to uncertain parameters, by means of either Taylor expansion or perturbation technique and evaluate the first and second order moments of the response by solving deterministic equations. Unfortunately, these methods lead to significant error when the standard deviation of uncertainties is relatively large. Herein, a first order perturbation approach is proposed. Comparisons with second-order perturbation approach and Monte Carlo simulation illustrate the efficiency of the proposed method. The results are discussed in order to investigate the influence of mass, damping and stiffness uncertainty on the dynamic response of a gear system.